Effects on Stocker Steer Performance While Consuming Essential Oil or Ionophore Minerals - Tatiana M. Jones; Jaymelynn K. Farney (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: To determine if essential oils produce the same performance for stocker steers as consuming an ionophore. Study Description: Steers (n = 281 head; 641 ± 10.3 lb) were assigned to one of two mineral treatments and grazed on tallgrass native range on eight pastures. Treatments consisted of the positive control of ionophore (lasalocid at 3.6 lb/ton) and essential oil (garlic oil at 3 lb/ton and essential oil blend at 6 lb/ton) in free-choice mineral. Steers were weighed at the beginning and end of the 92-day grazing period. Pasture biomass production and mineral intake were monitored weekly. The Bottom Line: Growth performance produced by essential oils in mineral and ionophores are similar when fed to growing stocker steers grazing tallgrass native range.
Keywords: lasalocid; tallgrass native range; garlic